Poly(Aspartic Acid) Functionalized Poly(ϵ-Caprolactone) Microspheres with Enhanced Hydroxyapatite Affinity as Bone Targeting Antibiotic Carriers - Stijn G. Rotman; Thomas F. Moriarty; Benjamin Nottelet; Dirk W. Grijpma; David Eglin; Olivier Guillaume (MDPI AG, 2020)
Bone infection is a feared complication for patients with surgically fixed bone fractures and local antibiotic delivery is important in prophylaxis and treatment of these infections. Recent studies indicated that Staphylococcus aureus can penetrate bone tissue through micron-sized canaliculi and evade systemic and currently available local antibiotic treatments. Targeting bacteria within the bone requires highly efficient delivery of antimicrobials to the infected bone tissue. In this work, a biodegradable microsphere carrier loaded with antibiotics and with specific affinity to bone mineral was developed. Two widely used antibiotics, i.e., Gentamicin-dioctyl sulfosuccinate (GM-AOT) and Ciprofloxacin (CF) were embedded in poly(ϵ-caprolactone) (PCL) microspheres fabricated by oil-in-water emulsion techniques with carboxylated poly(vinyl alcohol) (cPVA) as surfactant. The carboxylic acid groups present at the Poly(ϵ-caprolactone)/cPVA (PCL-cPVA) microsphere surface were functionalized with aspartic acid oligomers (ASP) granting bone targeting properties. We report on cPVA synthesis, microsphere formulation, and antibiotic loading of PCL/cPVA-ASP microspheres. Antibiotic loaded PCL/cPVA-ASP microspheres show sustained release of its antibiotic load and can inhibit bacterial growth in vitro for up to 6 days. PCL/cPVA-ASP microspheres show enhanced affinity to mineralized substrates compared to non-functionalized PCL/cPVA microspheres. These findings support further development of these bone targeting antibiotic carriers for potential treatment of persistent bone infections.